Effects of L-carnitine Supplementation in High-Fat Diet on Growth, Antioxidant Capacity and Lipid Metabolism of Golden Pompano (Trachinotus ovatus) - Chen, Xu; Niu, Jin; Wang, Jun; Zhao, Wei (Frontiers in Marine Science, 2022)
A 6-week feeding trial was carried out to investigate whether dietary L-carnitine supplementation could alleviate the adverse effects of high-lipid diet on the growth, antioxidation and lipid metabolism of Trachinotus ovatus. Four isonitrogenous experimental diets were performed as following: lipid positive (D1) contained 13 % lipid level; lipid negative (D2) contained 20 % lipid level; D3 diet contained 20 % lipid with 0.02 % L-carnitine; D4 diet contained 20 % lipid with 0.06 % L-carnitine. The final body weight, weight gain rate, specific growth ratio and feed intake of fish fed with D2 diet were significantly lower than that of other diet groups (P < 0.05). However, experimental diets were unable to change the feed conversion ratio and survival rate of fish (P > 0.05). The lowest value of crude protein and the highest value of crude lipid were found in fish fed with D2 diet (P < 0.05). However, there were no significant difference in the levels of crude protein and crude lipid among D1, D3 and D4 treatments (P > 0.05). Besides, higher levels of triglyceride and total cholesterol were found in D2 diet feeding fish than that of the other group (P < 0.05). Additionally, the superoxide dismutase activity, malondialdehyde content and the mRNA levels of manganese superoxide dismutase and glutathione peroxidase in fish fed with D2 diet were significantly higher than those fed with D1, D3 and D4 diets (P < 0.05). The mRNA levels of carnitine palmitoyl transferase 1 and peroxisome proliferator-activated receptors-alpha in fish fed with D2 diet were significantly higher than those fed with D1, D3 and D4 diets (P < 0.05). In conclusion, L-carnitine supplementation in high-lipid diet can alleviate the adverse effects of high-lipid diet on the growth performance and health of T. ovatus by promoting lipid hydrolysis, improving cholesterol transport and antioxidant capacity. Therefore, we recommended the 0.02 % addition level of L-carnitine for T. ovatus diet.